2006
DOI: 10.1002/hep.21451
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus resistance to entecavir in nucleoside naïve patients: Does it exist?

Abstract: A ntiviral therapy of chronic hepatitis B remains a major clinical challenge. 1 On the one hand, the development of new antivirals has been shown to be efficacious in controlling viral replication, decreasing the inflammatory activity within the liver, and preventing the progression of chronic hepatitis toward its main complications including decompensation of liver cirrhosis and development of hepatocellular carcinoma. 2 On the other hand, due to the unique mechanism of viral replication and persistence of HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…These lesions include lung adenomas and carcinomas, and liver adenomas and carcinomas. The cumulative human risk will require post-marketing surveillance 116. As for all antiviral agents, resistance might be encountered in clinical practice in slow or incomplete responders, albeit a relatively low rate 117.…”
Section: Entecavirmentioning
confidence: 99%
“…These lesions include lung adenomas and carcinomas, and liver adenomas and carcinomas. The cumulative human risk will require post-marketing surveillance 116. As for all antiviral agents, resistance might be encountered in clinical practice in slow or incomplete responders, albeit a relatively low rate 117.…”
Section: Entecavirmentioning
confidence: 99%
“…Furthermore, the selection rate of ETV resistant mutants is very low in naïve patients, but clinically relevant (9% at month 24) in patients with LMV resistance even if treated with higher ETV dose (1 mg vs 0.5 mg, [8]). Aminoacid substitutions within the YMDD motif of HBV polymerase that confer LMV resistance provide also the genetic background for ETV resistance, that occurs after additional substitutions at residues T184, S202 or M250 [11][12][13]. Accordingly, in 679 ETV naïve treated patient Colonno et al found that all viral breakthroughs with in vitro reduced susceptibility to ETV at week 96 were associated with baseline YMDD mutations [12].…”
mentioning
confidence: 94%
“…Thus studies of viral dynamics characterizing early viral kinetics could estimate drug efficacy quickly [29,35] and allow earlier treatment optimizations by increasing ADV dose, as proposed by Hézode et al or changing drugs [9,15] according to response profiles mainly in highly viremic patients. Finally, the characterization of viral quasispecies at baseline before rescue therapy will become mandatory as soon as a wider spectrum of anti-HBV drugs will be available and we could make a further step towards a more personalized anti-HBV therapy as already available in HIV infected patients [2,13,36,37].…”
mentioning
confidence: 99%
“…The emergence of resistant viral strains is an important consideration when selecting a nucleoside analogue. The very large pool of HBV in circulation, the rapid turnover rate, and the high error rate in HBV replication mean that any potential mutant, including those that give rise to drug resistance, may be present in a patient before he or she starts therapy [ 7 ]. The emergence of lamivudine resistance before and during therapy limits the usefulness of this drug.…”
Section: Introductionmentioning
confidence: 99%
“…Telbivudine selects for mutations in the YMDD motif and, although it is associated with lower resistance than lamivudine, recently reported virologic breakthrough due to resistance substitutions was 21.6% and 8.6% in HBeAg(+) and HBeAg(−) patients after 2 years of treatment [ 10 ]. The lowest reported rates of resistance after 5 years of treatment have been obtained with entecavir (<1%) [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%